Pentingnya Pengembangan Sumber Daya Manusia pada Lembaga Pendidikan - Juita, Dince Putri; Priya, Priya; Azwardi, Mayang; Amra, Abhanda (Indo-MathEdu Intellectuals Journal, 2024)
Education is the main foundation in building quality human resources. In the current era of global competition, the quality of education is the key to producing the next generation who are competent and competitive. This article aims to find out the importance of human resource development in educational institutions. This study uses a qualitative approach, where data collection uses library research. The main source of data for this research is the research articles published through the Journal and indexed by Google Scholar. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The findings of this study are that the development of educational human resources is the key to ensuring the quality and success of the education system. The development of educational human resources can be carried out through various programs, such as training, workshops, seminars, further studies, mentoring, and certification programs. The government, educational institutions, and professional organizations have an important role in designing and implementing effective and sustainable human resource development programs